THE INFLUENCE OF SOCIAL MEDIA ON HUMAN RIGHTS ACTIVISM AND POLITICAL PARTICIPATION IN NORTH CENTRAL - ALERO MARTHER RICHARDS; SIMON REAZANYI SHEYIGARI (International Studies Journal)
Internet is painstakingly an enormous expansion to human development. Literally, it is considered a useful key or essential to human development and social advancement causing massive revolution in the world. Over the years, the advent of Social media has pervaded, especially that of the young generation. It is against this background that this paper aims to study the influence of Social media and human right activism by Nigerian to gauge their usage in relation to political participation. For sampling purposes, the region is divided into six States. A survey research using questionnaire as instrument was used to obtain data, with 1182 respondents aged between 18 and 25 were randomly sampled from the six States of the region. The data were analysed descriptively and inferentially using SPSS 20.0. From the results, majority of the respondents, 89% are social media users having a social media account. A discouraging trend with regard to participation is the very low level of comments on general societal issues ranging from social issues, the environment to politics. The youth are more inclined to using the new media for entertainment and social networking. The paper recommends that Nigerian youth are exposed to political participation online, thus, they should be active in there doing. Also, it is time to shift to more empowered usage such as using the new media to engage with community leaders and politicians and comment on issues related to political development.